Prevalence of Glucose-6-Phosphate Dehydrogenase Deficiency Among Children in Eastern Saudi Arabia - Albagshi, Muneer H (Cureus, 2020)
Background Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common red blood cell enzyme deficiency worldwide. The disease is widely distributed in regions where malaria is prevalent, affecting mostly males because the enzyme is inherited as an X-link recessive pattern. In Saudi Arabia, we lack newborn screening (NBS) for G6PD deficiency, despite early reports about high prevalence. Methods This is a 10-year retrospective study of children who were screened for G6PD deficiency during their hospitalization between January 2008 to December 2017. The test was carried out using a qualitative fluorescence test suitable for mass screening to determine the prevalence of G6PD deficiency among the admitted children between 0 and 14 years of age. Results A total of 48,889 patients were screened which included 27,634 (56.5%) males and 21,255 (43.5%) females with a mean age of 1.93 + 3.98 years. The overall prevalence of G6PD deficiency was 25%, whereas it was 33.8% in the male subset and 13.2% in the female subset. Male sex was significantly correlated with G6PD deficiency. A total of 25,628 newborns were screened, with 14,219 (55.5%) males and 11,409 (44.5%) females, who had a G6PD deficiency prevalence of 18.8%. There was a G6PD deficiency prevalence of 26% in males and 9.9% in females. Conclusion The present study confirms the high prevalence of G6PD deficiency in our community. Therefore, we need to establish an NBS program to screen for G6PD deficiency in order to prevent neonatal hyperbilirubinemia encephalopathy, avoidable hemolytic episodes, and to increase awareness among health practitioners.